Multi-Role Collaboration of Ministries and Institutions in the Implementation of Agrarian Reform in Indonesia - Santosa, Sigit; Wicaksono, Arditya; Nugroho, Romi (BHUMI: Jurnal Agraria dan Pertanahan, 2021)
Agrarian reform is a homework that will not be completed only with sectoral approach. The real agrarian reform is not just dividing and legalizing the land, but making the land parcels have better access. This study used the collaboration theory of Russell M. Linden. The collaborative approach requires institutions to understand the basis of collaboration, create relationships, commitment and support among them built by collaborative leadership models. Agrarian reform must make Indonesian society better. Based on Linden’s qualitative descriptive method, there are several steps that can be adopted so as to make it easier to implement agrarian reform. The support of the governor/regent regulations on the above rules which substantially support the agrarian reform program will accelerate the implementation of the program. In addition, the division of roles and functions in the access corridor of reform requires a concrete conceptual foundation, easy to understand and firm in the form of rules that are accepted by all parties. Furthermore, in order to obtain a comprehensive and effective solution, the roles of ministries / institutions, the private sector, the community, NGOs, academics and mass media summarized in stakeholders need to be built systematically so as to eliminate the complexity of agrarian problems in Indonesia.